2014
DOI: 10.1007/s00300-014-1464-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation in faecal corticosterone metabolites in an Arctic seabird, the Little Auk (Alle alle) during the nesting period

Abstract: Glucocorticoids participate in the control of whole body homoeostasis and an organism's response to stress. Corticosterone, which is the principal glucocorticoid in birds, has been shown to increase in response to different energetic demands and perturbations that individuals have to cope with. In this study, a non-invasive method to examine the corticosterone secretion by measuring faecal corticosterone metabolites (FCM) has been established for an Arctic seabird, the Little Auk (Alle alle). A group-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
(74 reference statements)
0
16
0
Order By: Relevance
“…Experimental chicks before implantation and control chicks had similar levels of faecal corticosterone metabolites (Tukey and Kramer post hoc test, P = 0.97; Table 1). The increase in faecal corticosterone metabolites remained within the physiological range of this species (Kidawa et al 2014). Chicks implanted with the placebo pellet had similar concentrations before (median = 5.9, Q 1 -Q 3 : 4.6-8.9, n = 3) and 3 days after implantation (median = 6.89, Q 1 -Q 3 : 6.37-10.56, n = 3).…”
Section: Corticosterone Levelmentioning
confidence: 61%
See 4 more Smart Citations
“…Experimental chicks before implantation and control chicks had similar levels of faecal corticosterone metabolites (Tukey and Kramer post hoc test, P = 0.97; Table 1). The increase in faecal corticosterone metabolites remained within the physiological range of this species (Kidawa et al 2014). Chicks implanted with the placebo pellet had similar concentrations before (median = 5.9, Q 1 -Q 3 : 4.6-8.9, n = 3) and 3 days after implantation (median = 6.89, Q 1 -Q 3 : 6.37-10.56, n = 3).…”
Section: Corticosterone Levelmentioning
confidence: 61%
“…For example, Spée et al (2011) observed a 3.3-fold increase in circulating corticosterone levels within 3 days of pellet implantation. We chose chicks with a similar body mass for the study, because corticosterone levels vary between individuals with respect to their body mass (Kidawa et al 2014).…”
Section: Experiments With Chicksmentioning
confidence: 99%
See 3 more Smart Citations